Plasmon-induced light absorption in mid-infrared based on hexagonal-shape graphene. (13th November 2019) - Zhang, Zhaojian; Yang, Junbo; Han, Yunxin; He, Xin; Huang, Jie; Chen, Dingbo
Abstract: In this manuscript, we numerically propose the plasmon-induced light absorption based on periodical hexagonal-shape graphene. Under the both TM- and TE-polarization light, the patterned graphene can support surface plasmon resonances (SPRs) and introduce the light absorption in mid-infrared, and the mode properties of SPRs are also studied. Besides, the impacts of geometric parameters, Fermi levels as well as number of layers of graphene on absorption spectrum are thoroughly investigated. Finally, a metal layer is introduced at the bottom of the structure to enhance the absorption. Since such pattern graphene can be naturally grown and shaped due to the atom arrangement of graphene, it has low requirement of optical fabrication, and the supported double SPRs can also provide double-peak absorption. This work can find potential applications such as absorbers, photodetectors and biosensors.